ANALISIS PERBEDAAN HARGA SAHAM INDUSTRI HOTEL SEBELUM DAN SESUDAH PANDEMI COVID-19 PADA BURSA EFEK INDONESIA PERIODE 2019-2022 - Elma Abnaina; A. Frisa Ariza; Falah Falah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to test whether there are differences in the hotel industry's stock prices from the impact before and during the Covid-19 pandemic on the Indonesian Stock Exchange for the 2019-2022 period. The population of all stock prices consisting of 35 companies in the hotel industry sector are listed on the Indonesia Stock Exchange. The sample in this study closing price averaged daily, consisting of 48 samples with observations from 4 sector companies according to the criteria for the hotel industry listed on the Indonesia Stock Exchange in 2019 – 2022. This study used a paired sample t-test method. The results of the study show that there is a difference in the average value of the hotel industry stock price variable before and after the Covid-19 pandemic. The results show that there was a change during the Covid-19 pandemic with a Sig.(2tailed) value of 0.000, meaning it is less than 0.05, then Ho is rejected and H1 is accepted. That there is a significant difference between the results of the hotel industry stock prices before and after the Covid-19 pandemic.